Nurturing and Complexity – Threshold Concepts in Geriatric Medicine - Wilkinson, Iain (International Journal of Practice-based Learning in Health and Social Care, 2018)
Older adults make up the largest proportion of patients in UK hospitals. This will increase further over the next twenty years. To manage unwell older adults requires specific skills – yet many are looked after by non-specialists (be they doctors, nursing staff or therapists). Threshold Concepts (TCs) represent a means of examining the changes which take place in doctors in becoming ‘a geriatrician’, and thus may identify the key concepts to focus education on about the care of older patients. This article presents a qualitative study of trainers (consultants, the educational supervisors of junior doctors) and trainees (the junior doctors themselves). Twelve semi-structured interviews were analysed using a concept mapping technique in combination with a traditional qualitative analysis to identify TCs, which were then explored in more detail with a structured questionnaire delivered to trainees. The study shows that whilst there are a number of troublesome areas in geriatric medicine training, two concepts stood out as TCs. Appreciation of the ‘complexity of medical care’ of older patients and what that entails, and a new concept of ‘nurturing-care’ (focused on the wider care issues for the patient) – are proposed as TCs in geriatric medicine. Both have large degrees of tacit knowledge, and rely on a networked model of thinking. Identification of these TCs in geriatric medicine can allow a focused analysis of postgraduate medical curriculums to ensure they are covered by doctors of all grades to improve the standard of care of older patients in the UK health service.